Cytotoxic T-Cells in Peripheral Blood in Women with Endometriosis - Slabe, N.; Meden-Vrtovec, H.; Verdenik, I.; Kosir-Pogacnik, R.; Ihan, A. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: The etiology of endometriosis remains unknown, but increasing evidence suggests that immune regulation may be important. Our study aimed to evaluate peripheral blood lymphocyte subpopulations during the menstrual cycle in women with peritoneal and ovarian endometriosis relative to healthy women. Methods: In this study, 65 women with endometriosis (37 in the follicular phase and 28 in the luteal phase of the menstrual cycle) and 61 healthy women (33 in the follicular phase and 28 in the luteal phase) were enrolled. Flow cytometric analysis measured peripheral blood lymphocyte subpopulations. The serum levels of cortisol were also determined. Results: In healthy controls, we detected an increased concentration of cytotoxic (CD8+) T cells and activated (HLA-DR) T cells in the luteal phase compared with the follicular phase of the menstrual cycle (p = 0.020 and p = 0.045), whereas no such fluctuation was detected in endometriosis. However, a marked increase in regulatory T-cell concentration in the luteal phase was detected only in endometriosis patients (p = 0.005). Women with endometriosis had higher levels of serum cortisol (p = 0.022), which correlated with the concentration of regulatory T cells (p = 0.048). Conclusions: Women with endometriosis do not exhibit fluctuations in the concentrations of cytotoxic and activated peripheral blood lymphocytes during the menstrual cycle. The marked fluctuation of regulatory T cells detected in endometriosis could be attributed to altered immune response.
Keywords: endometriosis; gynecology; infertility; regulatory T cells; cell immunity